Strengths and Difficulties Questionnaire Parent Report (SDQ-PR) As Screening Instrument of Children Mental Health in Indonesia - Supra Wimbarti; Juliarni Siregar; Mistety Oktaviana; Regiastri Regiastri (Jurnal Psikologi, 2019)
This study aims at examining the agreement level between clinical diagnoses by a senior psychologist in the hospital and diagnoses/screening on Strengths and Difficulties Questionnaire conducted by parents. Using ICD 10 (Indonesian version) as the gold standard, a clinical child psychologist diagnosed 253 male and female elementary school children aged 7-14 years old. Parents of the same children were requested to fill-out the SDQ questionnaire (SDQ-PR).  Psychometric property of SDQ-PR was analyzed using Alpha Cronbach and Principal Axis Factoring Analysis. Screening quality of SDQ-PR was examined using Receiver Operating Characteristic (ROC), Likelihood Ratio (LR+ and LR-), and Chi-square. Reliabilities of SDQ-PR in all subscales were (α = 0.562 to α = 0.684) except subscale of peer-problem (α = 0.174). Different from the original version of SDQ-PR that consists of 5 subscales, this study revealed 8 subscales. LR and ROC analyses for hyperkinetic revealed LR+ = 1.84 and LR– = 0.51, sensitivity = 67.6% and specificity = 63.3% with cut-off score ≥ 6. For behavior disorder, the LR+ = 2.3, LR- = 0.42, sensitivity = 70.96%, and specificity = 69.15% with cut-off score ≥ 4. As for behavior disorder the LR+ = 1.07, LR- = 0.94, sensitivity = 50%, specificity 53.27% with cut-off score ≥ 4. Chi-square score indicated a significant correlation between SDQ-PR and the diagnoses from child psychologist for hyperkinetic and behavior disorder, but not for an emotional problem.